Absolutely small : how quantum theory explains our everyday world - Fayer, Michael D. (AMACOM, American Management Association, 2010)
This book makes the field of quantum theory understandable to nonscientists, without oversimplifying and without bogging down in complicated math. It uses clear explanations, real-world examples, and diagrams instead of dense equations to help you understand.